MENGENAL TANAH AIR MELALUI METODE BERCERITA DAN PERMAINAN BAGI ANAK USIA DINI - marshinta, Fransisca; Oktanisa , Silvana (Lembaga Dongan Dosen, 2023)
Globalization has greatly influenced the attitudes and behavior of the Gen Z generation, whose attitudes and sense of nationalism are starting to decline. Foreign culture, foreign food, clothes are some of the things that the Gen Z generation likes, it is more prestigious to use foreign brand products than domestic products and other attitudes/behaviors. The cultivation of nationalist values must be fostered and instilled from an early age. The target of the service is that Early Childhood Education (PAUD) students have nationalistic attitudes and behavior through storytelling methods using posters and story stages in presenting material about their homeland. The TGT cooperative learning game is a model used to determine the success of using the storytelling method in creating teamwork that does not differentiate between one another.